Biomarkers for the prediction of venous thromboembolism in the community. Issue 145 (September 2016) - Puurunen, Marja K.; Enserro, Danielle; Xanthakis, Vanessa; Larson, Martin G.; Benjamin, Emelia J.; Tofler, Geoffrey H.; Wollert, Kai C.; O'Donnell, Christopher J.; Vasan, Ramachandran S.
Abstract: Background &objectives: Venous and arterial thrombosis share common pathophysiology. Multiple biomarkers reflecting various biological pathways can predict arterial thrombosis. We studied whether this approach could identify persons at risk of first venous thromboembolism (VTE). Highlights: We studied multiple biomarkers in predicting venous thromboembolism (VTE). Community-based Framingham Heart Study Offspring cohort was studied. D-dimer and growth differentiation factor 15 (GDF-15) identify persons at VTE risk. The association of baseline GDF-15 with VTE is novel.